2018
DOI: 10.1016/j.juro.2018.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Host Factors on Robotic Partial Nephrectomy Outcomes: Comprehensive Systematic Review and Meta-Analysis

Abstract: Robotic partial nephrectomy outcomes are impacted by host factors, including tumor and patient characteristics. Awareness of this increased risk and its mitigation with expert patient selection are important for excellent robotic partial nephrectomy outcomes. Our meta-analysis provides comprehensive, objective, summary data of 10,506 patients, detailing discrete outcomes for discrete host factors to better inform urologists and patients considering robotic partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 47 publications
7
32
0
1
Order By: Relevance
“…Conversely, the SPARE system was not an independent predictor of renal function impairment. These data concur with other studies showing that the original PADUA score was not a predictor of 3-month renal function impairment [5,23]. Therefore, tumour CSA could help surgeons to tailor Limitations of the present study include the retrospective design and the lack of central imaging review to assign the variables included in the PADUA score and to calculate the tumour CSA.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, the SPARE system was not an independent predictor of renal function impairment. These data concur with other studies showing that the original PADUA score was not a predictor of 3-month renal function impairment [5,23]. Therefore, tumour CSA could help surgeons to tailor Limitations of the present study include the retrospective design and the lack of central imaging review to assign the variables included in the PADUA score and to calculate the tumour CSA.…”
Section: Discussionsupporting
confidence: 86%
“…With regard to the clinical implications of these findings, and specifically the role of the nephrometry score in predicting postoperative outcomes, the receiver-operating characteristic curves demonstrated that both the 2D and the 3D nephrometry score were correlated with overall and major complications (AUCs calculated with 3D VMs ranging from 0.67 to 0.84), confirming the findings in the literature [29,30]. Nephrometry category, as assessed by the two different imaging tools, was also considered in order to evaluate whether the 2D-or 3D-based category was more closely related to postoperative outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…PN is a complex surgical intervention and the prediction of surgical complication rate, in addition to the oncological and functional outcomes, is paramount to assess the risk/benefit ratio of PN compared to RN [13,14]. In our present study, the overall postoperative surgical complication rate was 10.2% and the major surgical postoperative complication rate was 2.5%.…”
Section: Discussionmentioning
confidence: 54%